Across-language masculinity of oceans and femininity of guitars: Exploring grammatical gender universalities - Dubenko, Elena (Frontiers in Psychology, 2022)
This is the first cross-language study to reveal nouns with invariable masculine or feminine grammatical gender assignments in nine gendered languages from different groups of one linguistic family. It evidences that many cases of gender universality have semantic motivation-an entity’s grammatical gender correlates with either traditional masculine/feminine connotations, or cultural and symbolic implications. The study’s findings also testify thematic preferences: most masculine grammatical gender universalities are found for the nouns denoting artifacts, whereas most feminine universalities are identified for abstract concepts. The apparent existence of grammatical gender universalities has a cognitive significance. From a psycholinguistic perspective, grammatical gender is viewed as a built-in personification pattern for speakers’ mental representations. This research presents cross-linguistic constants in conceptualizing the natural kinds, artifacts, and abstract concepts denoted by the considered nouns, as “male” or “female”.